Effect of Specific Formulated Feed to Alter the Glucose, Triglycerides and Total Cholesterol Level in Rat (EFEK FORMULASI PAKAN TIKUS TERHADAP PERUBAHAN KADAR GLUKOSA, TRIGLISERIDA DAN KOLESTEROL TOTAL) - Rahmi, Jihan Mudrika; Lesmana, Ronny; Goenawan, Hana; Setiawan, Setiawan; Tarawan, Vita Murniati; Wismandanu, Okta; Supratman, Unang (Jurnal Veteriner; Vol 20 No 2 (2019)DO - 10.19087/jveteriner.2019.20.2.179, 2019)
Understanding the molecular mechanism of type 2 diabetes mellitus using human sample is very difficult, therefore utilization of animal model can be the solution for studying diabetes mellitus. However, there is still limited option of the animal model that can describe the process of type 2 diabetes mellitus. The aim of this study is to develop a formulated feed with increased glucose, triglycerides, and total cholesterol as characteristics of type 2 diabetes mellitus. This study was done using a descriptive method and experimental study design for 8 weeks. Total 9 male and 12 female Wistar rats were randomly divided into 3 groups: 1 control group and 2 treatment group (formula 1: high carbohydrate, formula 2: high fat). The increase of delta mean body weight was higher in the group given formula 1 for both male and female rats (f: 52g, m: 71.67g). The glucose level was increase from 4th- 8th week in both gender of rats and higher in the group given formula 1 of female rats (4W: 221.13 mg/dl; 8W: 249.83 mg/dl). The triglycerides level was increased from 4th to 8th week and higher in group given formula 2 either male (4W: 37.42 mg/dl; 8W: 58.92 mg/dl) but not in female rats (4W: 76.78 mg/dl; 8W: 71.22 mg/dl). The cholesterol total level also increased in male (4W: 93.05 mg/dl; 8W: 282.5 mg/dl) and female (4W: 101.58 mg/dl; 8W: 227.17 mg/dl) rats and higher in the group given formula 1.  In conclussio, either high carbohydrate or high fat pellet showed potential capability to increase the glucose, triglyceride and total cholesterol level especially in female rats.